Autoimmunity and Inflammation Link to Cardiovascular Disease Risk in Rheumatoid Arthritis - Daniel J. DeMizio; Laura B. Geraldino-Pardilla (Rheumatology and Therapy, 2019)
Abstract Rheumatoid arthritis (RA) patients have a 50% increased risk of cardiovascular (CV)-related morbidity and mortality. This excess CV risk is closely linked to RA disease severity and chronic inflammation, hence is largely underestimated by traditional risk calculators such as the Framingham Risk Score. Epidemiological studies have shown that patients with RA are more likely to have silent ischemic heart disease, develop heart failure, and experience sudden death compared with controls. Elevations in pro-inflammatory cytokines, circulating autoantibodies, and specific T cell subsets, are believed to drive these findings by promoting atherosclerotic plaque formation and cardiac remodeling. Current European League Against Rheumatism (EULAR) guidelines state that rheumatologists are responsible for the assessment and coordination of CV disease (CVD) risk management in patients with RA, yet the optimal means to do so remain unclear. While these guidelines focus on disease activity control to mitigate excess CV risk, rather than providing a precise algorithm for choice of therapy, studies suggest a differential impact on CV risk of non-biologic disease-modifying anti-rheumatic drugs (DMARDs), biologic DMARDs, and small molecule-based therapy. In this review, we explore the mechanisms linking the pathophysiologic intrinsic features of RA with the increased CVD risk in this population, and the impact of different RA therapies on CV outcomes.